Geliat UMKM : Pelatihan dan Pendampingan Penyusunan Laporan Keuangan Berdasarkan PSAK EMKM pada UMKM Laura Pulau Harapan Maninjau - Sri Madona Saleh; Sri Adella Fitri; Nasfizar Guspendri; Mega Rahmi (Jurnal Abdimas Adpi Sosial dan Humaniora, 2023)
One of Indonesia's sources of economic strength that has endured the epidemic that has been going on since 2020 is MSMEs. MSMEs are a type of industry that can take on labor thanks to labor-intensive business procedures. The UMKM Laura Pulau Harapan is one of the MSMEs found near Lake Maninjau. This MSME works in the food industry and relies on "Rinuak," a raw material source that comes from Lake Maninjau. Fish of the Rinuak variety can be found at Lake Maninjau. Rinuak sales are no longer dependent on the availability of raw materials because MSME companies have transformed it by turning it into several types of cuisine. UMKM Stretching was done by UMKM when processing Rinuak. Laura Pulau Harapan, manager of MSME, thinks that MSME can be grown even further but is limited by the framework issue. This is a result of managers' insufficient awareness of recording prior to the creation of MSME Financial Reports. There is no description of the business performance to date due to the lack of MSME Financial Reports. Managers are unable to manually or systematically record anything. This is because the manager was unable to record and prepare these financial reports and didn't understand how to do so. The team delivering training trains managers so they can record and compile financial reports using the mentoring approach and FGD. Managers have benefited from this training in that they have successfully completed various recording processes.